Determinants of Pneumonia Status in Under-five Children in Indonesia - Ananda, Intan Putri; Budyanra, Budyanra (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2024)
Background: Pneumonia is a communicable disease that causes the largest under-five children death in the world. Meanwhile, Indonesia contributed 19.000 cases of under-five deaths due to pneumonia in 2018. Pneumonia can inhibit the growth and development in under-five children, cause decreased lung function or even lead to death. The pneumonia symptoms is less specific and almost the same as the flu or a common cough, makes this disease difficult to detect and difficult to treat optimally. This study was aimed to determine variables that affect the pneumonia in under-five children in Indonesia in 2018.Methods: This study used descriptive analysis and multilevel binary logistic regression. It used secondary data from the Riskesdas 2018, publication of Profil Kesehatan Indonesia 2018, and official website of Badan Pusat StatistikResult: The results indicated that in 2018, there were about 6.4 percent of under-five children who experienced pneumonia. The age of under-five children, gender, nutritional status, maternal education level, type of residence, house’s ventilation, and poverty rate per province significantly affected the status of pneumonia in under-five children in Indonesia.Conclusion : This study was expected to be able to increase public awareness about pneumonia in under-five children and can prevent under-five deaths due to pneumonia. Further research can use more up-to-date primary data and can also focus on provinces that have high rates of pneumonia in under-five children.